Analysis of Customer Satisfaction Using the Modified Servqual Method (Case Study at Waroeng Spesial Sambal Ss) - Ridho Dimas Sofwan; Agus Mansur; Imam Djati Widodo (Universitas Muhammadiyah Sidoarjo, 2019)
Restaurant business is one of the types of businesses that continues to grow in Indonesia. With the potential of this type of business, restaurants are competing to provide the best service for consumers. Waroeng Special Sambal is one of the restaurants that located in Yogyakarta. Waroeng SS has been serving consumers for years, nevertheless there are things that are felt not to meet with consumer expectations. The purpose of this study is to determine the quality of service in Waroeng SS restaurant, determine the priority of improvements, and determine the perceptions and expectations of consumers using the modified servqual method. The result of this study indicate that the tangible dimension for direct consumers has the lowest value and for consumers nearby, the dimensions that have the lowest performance is responsiveness. The attribute that has the lowest value is “the size of parking space” for direct consumers and “the parking space for vehicle onubstructive” for consumers nearby.